The Routledge Handbook of Infrastructure Design Global Perspectives from Architecture History - Heathcott, Joseph (Taylor & Francis, 2022)
The Routledge Handbook of Infrastructure Design explores the multifaceted nature of infrastructure through the global lens of architectural history. Infrastructure holds the world together. Yet even as it connects some people, it divides others, sorting access and connectivity through varied social categories such as class, race, gender, and citizenship. This collection examines themes across broad spans of time, raises questions of linkage and scale, investigates infrastructure as phenomenon and affect, and traces the interrelation of aesthetics, technology, and power. With a diverse range of contributions from 33 scholars, this volume presents new research from regions including South and East Asia, Sub-Saharan Africa, South America, North America, Western Europe, the Middle East, and the former Soviet Union. This extraordinary group of authors bring close attention to the materials, functions, and aesthetics of infrastructure systems as these unfold within their cultural and political contexts. They provide not only new knowledge of specific artifacts, such as the Valens Aqueduct, the Hong Kong waterfront, and the Pan-American Highway, but also new ways of conceptualizing, studying, and understanding infrastructure as a worlding process. The Routledge Handbook of Infrastructure Design provides richly textured, thoroughly evidenced, and imaginatively drawn arguments that deepen our understanding of the role of infrastructure in creating the world in which we live. It is a must-read for academics and students.